Russian Energy and Climate Policy Remains Inconsistent: Challenges for the EU - Christian von Hirschhausen; Claudia Kemfert; Franziska Holz (Weekly Report, 2005)
The relations between Russia and the EU with respect to energy and climate policies have been characterized in recent months by two phenomena. On the one hand, the EU has to deal with questions regarding the security of energy supply. The Russian government's high-handed treatment of domestic and foreign energy enterprises operating in the country is irritating potential investors. There is reason to seriously doubt that genuine progress is being made with market economy reforms in the Russian energy sector. While Russia will remain an important energy supplier for Germany and the EU in the medium term, the importance of other crude oil and natural gas exporters, including some North African countries, is likely to grow. On the other hand, it can be noted positively that Russia (in response to intense pressure from the EU) has ratified the Kyoto Protocol on reduction of greenhouse gas emissions, enabling the protocol to enter into force in February 2005. But Russia is expected to withhold emissions permits for strategic reasons, i.e. in order to allow the price of CO2 certificates to rise. The value of the CO2 emissions permits allocated to Russia under the Kyoto Protocol could earn the country a revenue of up to 30 billion euro. However, whether this will actually happen will also depend on the National Allocation Plans of the EU member states.
Keywords: 330